PROFIL FITOKIMIA DAN ANALISIS TOKSISITAS Ficus racemosa L. MENGGUNAKAN METODE BRINE SHRIMP (Artemia salina) LETHALITY TEST - Suryani, Novia (ALOTROP, 2023)
[Phytochemical Profile and Toxicity Analysis of Figs (Ficus racemosa L.) Using Shrimp (Artemia salina) Brine Method Lethality Test] A traditional plant, Ficus racemosa L., known as the ara plant in West Nusa Tenggara, is potentially beneficial as a drug candidate, which is one option to develop the biodiversity of natural ingredients in Indonesia. The extract was produced by maceration method with ethanol 96% solvent. Furthermore, they partitioned using various solvents, n-hexane, ethyl acetate, and chloroform. The presence or absence of secondary metabolite is determined by the phytochemical screening test.  Meanwhile, the Brine Shrimp Lethality Test (BSLT) is a toxicity screening to determine the LC50 of extract and their partition with various concentrations used were 50, 100, 250, 500, and 1000 ppm. The metabolite secondary flavonoids, alkaloids, and saponins are confirmed. The analysis showed that LC50 of extract was 218,34 ppm; n-hexane fraction was 413,57 ppm; ethyl acetate fraction was 309.51 ppm; and chloroform fraction was 314.60 ppm; all had toxic potential.